A Novel Endovascular Therapy Strategy for Acute Ischemic Stroke Due to Intracranial Atherosclerosis-Related Large Vessel Occlusion: Stent-Pass-Aspiration-resCuE-Micowire-Angioplasty (SPACEMAN) Technique - Wu, Yingchun; Wang, Junmei; Sun, Rui; Feng, Guanqing; Li, Wenzhao; Gui, Yuejiang; Zheng, Yanan (Frontiers in Neurology, 2022)
Background: There is no clear consensus on the optimal endovascular treatment strategy for patients with ischemic stroke caused by ICAS-related large vessel occlusion (LVO). SPACEMAN, a novel thrombectomy technique that entails passing an aspiration catheter over the stent retriever and then retaining the microwire for angioplasty, has not been described. The aim of this prospective study was to evaluate our initial application of SPACEMAN and compare this technique with the Solumbra technique. Methods: Forty-four consecutive patients with acute ischemic stroke resulting from ICAS-related LVO were randomly divided into two groups: Solumbra group (n=22) and SPACEMAN group (n=22). Demographic and clinical data were prospectively collected. Modified Rankin Scale (mRS) score of ≤ 2 of anterior circulation and mRS score ≤ 3 of posterior circulation at 3 months post-discharge was regarded as good prognosis. Results: The SPACEMAN group showed reduced mean time from femoral access to recanalization compared with the Solumbra group (39.55±10.63min vs. 50.73±9.89 min, P=0.001). The overall recanalization rate in the entire cohort was 93.18% (41/44). At 3-month follow-up, the overall good prognosis rate was 47.73%; 13 patients (59.09%) in the SPACEMAN group and 8 (36.36%) in the Solumbra group showed good prognosis. One patient in the SPACEMAN group (4.55%) and two patients in the Solumbra group (9.09%) developed symptomatic intracranial hemorrhage. The overall mortality rate was 4.55% (2/44). Conclusions: This study suggests that SPACEMAN exhibits a shorter operation revascularization time than the standard thrombectomy. Complications and prognosis were comparable between the two groups. The safety and efficacy of this novel technique need to be studied in larger patient series.